Sprint capacity differences in soccer players with distinct sprint performances - Aguiló, A.; Pasquarelli, B. N.; Stanganelli, L. C. R.; Dourado, A. C.; Andrade, C. A.; Tauler, P. (Archivos de medicina del deporte, 2008)
Introduction: Sprint capacity of soccer players is an important variable in modern soccer and could be crucial in critical duels which might influence the results of a game. The aim of this study was to compare the sprint capacity of professional soccer players with different sprint performances. Materials and methods: 143 professional soccer players of the 1st Brazilian Regional Division (age: 23.91 ± 3.95y; height: 177 ± 0.06cm; body weight: 73.28 ± 6.56kg) performed the 30m linear sprint test and were timed by photocells positioned at starting line (0m) and at 10, 20 and 30m of distance. For data analysis, the players were divided in quartiles according to their performance (final time) on 30m sprint test and they were classified into: Q1 </= 4.06s, n=38; Q2 </= 4.15s, n=37; Q3 </=4.24s, n=31; Q4 </= 4.72, n=37. In order to compare the average time among the groups in the different distances, the ANOVA (one-way) was used and the Tukey`s post-hoc test was utilized to determine pair wise differences (p<0.05). Results: All groups were significantly different from each other in all the distances (Table 1). The Table 2 shows the average distances when comparing the athletes of the Q1 to the athletes of Q2, Q3 and Q4 athletes. Conclusions: The fastest players at the 30m sprinting test showed the fastest as well in all other distances and this may be advantage when performing short distances during the game